Recirculation in a full scale rotating biological contactor for nitrogen removal - Chan, Kwok Leung (Cranfield University, 2009)
The effect of an internal recirculation on the total nitrogen removal efficiency in a full scale Rotating Biological Contactor (RBC). The study consists of two trials using two RBC units in parallel, with one acting as a control and the other with a recycle system installed. Trial 1 was to recycle nitrate rich effluent from the humus tank back to the septic tank at the front of the unit, where denitrification occurs using the raw wastewater as a carbon source. TN removal had improved from 25% to 74% when the recycle ratio (R) was increased from 0 to 2. There is no noticeable effect on BOD5 concentration in the effluent as R increases, maintaining a steady 96% removal rate. The effluent had shown a slight increase in turbidity as R increase. Trial 2 was to recycle from the biozone to the septic tank. An overall reduction in removal efficiencies in the test unit have shown that recycling directly from the biozone could not achieve a better performance. Recycling from the biozone had also induced simultaneous nitrification and denitrification in the septic tank, resulting in a 50% reduction in BOD5 and TN prior entering the biozone.
Keywords: internal recirculation; nitrate rich effluent; recycle system; denitrification; biozone; removal efficiencies